Lubricity effect of carbon dioxide used as an environmentally friendly refrigerant in air-conditioning and refrigeration compressors (2010)
Environmental concerns have increased the interest in alternative natural refrigerants for air-conditioning and refrigeration compressors. Carbon dioxide (CO2) or R744 is an attractive candidate to replace harmful hydrofluorocarbon refrigerants, which will need to be replaced in the near future due to their high global warming potential. In this paper the tribological behavior of gray cast iron in the presence of CO2 under unlubricated conditions was investigated. Specifically different regions of the CO2 pressure–temperature (P–T) phase diagram were studied to understand the role of pressure, temperature, CO2 mass, and the chemical interaction of gray cast iron with CO2, focusing on their impact on the friction and wear behavior. It was found that friction decreases significantly when CO2 pressure and temperature approach the gas–liquid transition in the P–T phase diagram, thus exhibiting a form of “superlubricity.” Through X-ray photoelectron spectroscopy it was found that an increase in CO2 pressure causes partial transformation of iron oxides into iron carbonates which have a positive effect on the tribological performance. The thickness of the tribolayer film, formed in the contact zone, was evaluated using Focus Ion Beam and it was found to be of the order of 0.5 μm